Traditional Thai herbal medicine for treating COVID-19 - Phayong Thepaksorn, Katanchalee Thabsri, Piyachat Evelyn Denbaes, Suwannee Sroisong, Pussadee Srathong, Suriyan Sukati (Journal of Applied Pharmaceutical Science, 2023)
Traditional Thai herbs, especially their phytochemicals, are believed to have a wide range of antimicrobial, anti-inflammatory, antioxidant, and antiviral properties. This review focuses on traditional Thai herbs for the potential treatment of coronavirus disease 2019 (COVID-19). Thai herbal therapies, including traditional Thai medicines, have been studied, investigated, and used to advance scientific knowledge. Specifically, Thai herbs, including Andrographis paniculata, Boesenbergia rotunda, Phyllanthus amarus, Phyllanthus emblica L., Citrus medica, Zingiber officinale, Rheum officinale Baill., and Kerra capsule, have been documented and used in the treatment of severe acute respiratory syndrome (SARS)-CoV-2. Traditional Thai herbs are believed to have various antiviral properties, and these herbs show promise as defense mechanisms against SARS-CoV-2. The focus of this review is on the traditional Thai herbs that have anti-viral properties and may have an impact on COVID-19.
Keywords: Thai herbs, Kerra capsule, antiviral, COVID-19